Promotion Strategy For Maslahah Gold Installment Products At BSI KCP Probolinggo Kraksaan - Achmad Febriyanto; Salimatul Imaniah (International Journal of Science and Environment (IJSE), 2025)
In line with the rapid advancement of technology and economy, sales promotion has become a crucial aspect in attracting public interest to invest in gold installment systems. The purpose of this research is to examine the effectiveness of sales promotion and how BSI measures the success of its implemented strategies. The concept of maslahah in Islamic economic systems serves as the primary foundation for developing sharia-compliant financial products. This principle emphasizes that products should offer multiple benefits beyond financial gains, including benefits to society in economic, social, and welfare aspects. This research employs a descriptive qualitative method, with data collection conducted through literature studies, interviews with the PA team and employees of BSI KCP Probolinggo Kraksaan, and observation. The results show that BSI KCP Probolinggo Kraksaan implements promotional strategies, including personal selling, advertising, public relations, and direct sales. The promotional strategies used are based on the concept of maslahah, also Known as sharia compliance. Although there are challenges in increasing public awareness about gold investments, the strategies implemented can increase sales of gold installment products and provide better education to customers. The strategies employed by BSI KCP Probolinggo Kraksaan to educate public understanding include transparency and sharia compliance, partnerships with sharia institutions and Muslim communities, and social-based incentive programs.